2017
DOI: 10.1039/c7ra07024a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-sensitive magnetic nanoparticles for dual-modal tumor imaging and therapy

Abstract: “Nanotheranostics” has attracted much attention due to the development of nanomaterials with integrated diagnostic and therapeutic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
1
16
2
Order By: Relevance
“…To our knowledge, no CEUS imaging of actively targeted NDs using ODV has been reported and the majority of these particles were evaluated after passive accumulation in the tumor or after intra-tumoral injection in the tumor bed. Zhao et al and Xu et al reported the development of PLGA-based NPs infused with perfluorohexane (PFH) or PFP NDs respectively [26,32]. The photo-absorber in both cases were iron oxide NPs encapsulated within the NDs which provided means for MRI and CEUS imaging.…”
Section: Optical Droplet Vaporization (Odv)mentioning
confidence: 99%
“…To our knowledge, no CEUS imaging of actively targeted NDs using ODV has been reported and the majority of these particles were evaluated after passive accumulation in the tumor or after intra-tumoral injection in the tumor bed. Zhao et al and Xu et al reported the development of PLGA-based NPs infused with perfluorohexane (PFH) or PFP NDs respectively [26,32]. The photo-absorber in both cases were iron oxide NPs encapsulated within the NDs which provided means for MRI and CEUS imaging.…”
Section: Optical Droplet Vaporization (Odv)mentioning
confidence: 99%
“…Poly-lactide-co-glycolide (PLGA) is one of the most widely used nanocarriers due to its excellent biodegradability and biocompatibility. PLGA is also approved by the FDA, and its perfect loading capacity has been proven by many successful NPs established by previous researchers 12 , 14 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…9 It is noteworthy that our research group and other research groups reported that microbubbles loaded with Fe 3 O 4 nanoparticles exhibited advantages such as better contrast for US imaging and an increased transversal relaxation rate in MR. 8,10,11 Furthermore, our research group and Zhao et al reported Fe 3 O 4 nanoparticles could be employed for hyperthermia therapy (HTT), which applied localized thermal energy to burn cancer cells that resulted in cell protein denaturation and coagulation necrosis. 12,13 In these studies, peruorocarbon (PFC) liquid droplets, which could produce excellent ultrasound imaging contrast by transforming from a liquid to gas state via acoustic or optical vaporization, 14,15 were instead of gas encapsulated microbubbles as ultrasound contrast agents. Rapoport et al reported phase-shi PFC nanoemulsions combined properties of polymeric drug carriers, ultrasound imaging contrast agents, and enhancers of ultrasound-mediated drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The most used phase-shi liquid core is peruoropentane (PFP) with a boiling point of approximately 29 C. The PFP nanodroplets easily convert into nano and/or microbubbles upon heating to physiological temperatures. 12,15,16 Near-infrared (NIR) refers to electromagnetic radiation in the region between 780 and 2526 nm. NIR light has the characteristics of controllable radiation scope, high penetration of cancer tissue without obvious damage to the surrounding normal tissues and organs and can potentially be used to treat tumors without surgical resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation